Modeling and Simulation of Traffic flow: A Case Study - First Ring Road in Downtown Madinah - M. Nomani, Kabir; Alginahi, Yasser M.; Mohamed, Ali I. (Penerbit UMP, 2016)
Traffic assessment is extremely important for the performance evaluation of vehicle flow on a road network. This paper presents an assessment of traffic flow on the busiest road i.e., First Ring Road located at the central area of Madinah in Saudi Arabia. In this paper, the assessment of traffic-flow is performed by evaluating and analyzing the traffic on First Ring Road. This includes investigating the number of vehicles entering and exiting the central area through First Ring Road, the arrangements of the road, percentage of traffic entering versus exiting, etc. In addition, a new model for the traffic distribution along the roads intersecting with First Ring Road was built based on optimization. Our optimization model was formulated as a minimization problem of the difference between the measured number of vehicles and the sum of portions of vehicles from all entrances of First Ring Road that move out from each road. A simulation program was developed using Matlab to solve the optimization model. The simulation results show good agreement with the corresponding measurement data of vehicles at First Ring Road. Thus, our model can be used as a prediction model of vehicle movements.